Identification of heat-tolerant mungbean genotypes through morpho-physiological evaluation and key gene expression analysis - Bhardwaj, Ragini; Gayacharan,; Gawade, Bharat H.; Pathania, Pooja; Talukdar, Akshay; Kumar, Prakash; Khan, Suphiya; Singh, Gyanendra Pratap (Frontiers in Genetics, 2024)
Mungbean plays a significant role in global food and nutritional security. However, the recent drastic rise in atmospheric temperature has posed an imminent threat to mungbean cultivation. Therefore, this study investigates the growth and physiological changes of 87 mungbean germplasm lines under heat stress. Genotypes were examined using parameters including leaf area, chlorophyll content, membrane stability index (MSI), stomatal conductance, pollen viability, number of pods per clusterpod bunch size, number of pods per plant total pod count/plan, number of seeds/pod, 100-seed weight, and grain yield/plant under heat stress and control environments. A wide range of variation was observed for these traits among genotypes under heat stress and control environments. Genotypes were also identified with variable responses under both environments. The phenotypic expression of selected promising accessions was also validated in control environment conditions at the National Phytotron facility. The selected promising genotypes viz., IC76475, IC418452, and IC489062 validated their heat tolerance behavior for key candidate genes revealed by quantitative real-time PCR (qRT-PCR). These mungbean genotypes can act as potential resources in the mungbean improvement programs for heat stress tolerance. This study also provides a comprehensive understanding of the key mechanisms underlying heat tolerance in mungbean.